Numerical Study of the Impact on Cooling Behaviour of Vent-Holes Design of Fruit Packaging Boxes - Curto, João Paulo (2021)
Fruit packaging is highly impactful in temperature and humidity distribution for post-harvest fresh fruit cooling and conservation. It is also the most flexible part on fruit production and should be able to increase shelf-life by deterring adverse conditions. However, packaging thermal performance during cold storage where it is displayed to the internal airflow is influenced by the size and position of vent-holes. In this study airflow inside the fruit box and fruits thermal behaviour are evaluated in order to determine differences between three prototype package models. Models differ from each other by the holes' configuration and size. Furthermore, models' performance is compared to a commercially available box of similar dimensions. Experimental tests were carried out in three stacked boxes, equipped with temperature and humidity sensors, and placed inside a refrigeration chamber with forced air cooling. Packaging box CFD models of each prototype wall were developed to predict the airflow and heat transfer during storage in a refrigeration chamber. Models predictions were validated by experiments results. According with simulation results, all prototypes have better thermal performance than the commercial model. However, significant performance differences between prototype walls were found. Fewer, larger and strategically distributed vent-holes allow a better result in terms of temperature homogeneity inside the box and significant reduction in fruit cooling times.